The flourish, failure and future phases of joint internationalisation: a longitudinal case study on collective international opportunity recognition - Haaja Eini; Nummela Niina (Inderscience, 2022)
This study explores how collective international opportunity recognition emerges and evolves over time. We investigate the role of mental images and sensemaking in such a process among a group of Finnish maritime sector SMEs. We propose that collective international opportunity recognition builds on encountered events, individual sensemaking and inter-firm sensemaking. Critical events trigger sensemaking which is based on managers' mental images of the opportunity context. Sensemaking emerges at the individual-level as auspicious or ominous sensemaking, and at the inter-firm-level as collective or fragmented sensemaking. Auspicious, collective sensemaking supports continued collective international opportunity recognition and the joint internationalisation of SMEs. Managers' mental images evolve with sensemaking, which together with new events affects the recognition of joint internationalisation opportunities in the future.